The Effectiveness of Entrepreneurship Teaching Materials for Engineering Students at Faculty of Engineering of Universitas Negeri Semarang - Rachmawati, Rina (Dinamika Pendidikan, 2016)
This research aims to test the effectiveness of entrepreneurship teaching materials for students majoring on Family Wealth Education Department at Faculty of Engineering, Universtas Negeri Semarang. Entrepreneurship teaching materials were developed by researchers by using ADDIE model, and the research only focused on the effectiveness of entrepreneurship teaching materials. It was a quasi-experimental study with a before-after or one group pretest-posttest technique. The research was conducted for 4th semester students of Family Wealth Education Department who studied entrepreneurship subject. In the experimental group, students were taught by teaching materials which were developed by the references of entrepreneurship subject on Higher Education and also was adapted by the conditions of students. Data were collected by using test, questionnaires and learning observation sheets. To test the hypothesis, it used paired t-test analysis and gain-score testing to measure the effectiveness of teaching materials in supporting the Entrepreneurship subject at Family Wealth Education Department of Faculty of Engineering. Findings show that the entrepreneurship teaching materials are effective and the results of other analysis show that students’ scores are increased from pre-test to post-test who were taught with Entrepreneurship teaching materials.